Practitioner Review: Treatment of chronic insomnia in children and adolescents with neurodevelopmental disabilities. (18th September 2017) - Bruni, Oliviero; Angriman, Marco; Calisti, Fabrizio; Comandini, Alessandro; Esposito, Giovanna; Cortese, Samuele; Ferri, Raffaele
Abstract : Background: Sleep disturbances, in particular insomnia, represent a common problem in children with neurodevelopmental disabilities (NDDs). Currently, there are no approved medications for insomnia in children by the US Food and Drug Administration or European Medicines Agency and therefore they are prescribed off‐label. We critically reviewed pediatric literature on drugs as well as nonpharmacological (behavioral) interventions used for sleep disturbances in children with NDDs. Methods: PubMed, Ovid (including PsycINFO, Ovid MEDLINE ®, and Embase), and Web of Knowledge databases were searched through February 12, 2017, with no language restrictions. Two authors independently and blindly performed the screening. Results: Good sleep practices and behavioral interventions, supported by moderate‐to‐low level evidence, are the first recommended treatments for pediatric insomnia but they are often challenging to implement. Antihistamine agents, such as hydroxyzine or diphenhydramine, are the most widely prescribed sedatives in the pediatric practice but evidence supporting their use is still limited. An increasing body of evidence supports melatonin as the safest choice for children with NDDs. Benzodiazepines are not recommended in children and should only be used for transient insomnia, especially if daytime anxiety is present. Only few studies have been carried out in children's and adolescents' zolpidem, zaleplon, and eszopiclone, with contrasting results. Limited evidence supports the use of alpha‐agonists such as clonidine to improve sleep onset latency, especially in attention deficit/hyperactivity disorder subjects. Tricyclic antidepressants, used in adults with insomnia, are not recommended in children because of their safety profile. Trazodone and mirtazapine hold promise but require further studies. Conclusions: Here, we provided a tentative guide for the use of drugs for insomnia in children with NDDs. Well‐controlled studies employing both objective polysomnography and subjective sleep measures are needed to determine the efficacy, effectiveness, and safety of the currently prescribed pediatric sleep medicines in children with NDDs.